2016
DOI: 10.1080/21592799.2016.1181700
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric properties of PH domains in Arf regulatory proteins

Abstract: Pleckstrin Homology (PH) domains bind phospholipids and proteins. They are critical regulatory elements of a number enzymes including guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) for Ras-superfamily guanine nucleotide binding proteins such as ADP-ribosylation factors (Arfs). Recent studies have indicated that many PH domains may bind more than one ligand cooperatively. Here we discuss the molecular basis of PH domain-dependent allosteric behavior of 2 ADPribosylation factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 113 publications
(149 reference statements)
1
9
0
Order By: Relevance
“…Conversely, increased PI(4,5)P 2 production caused Rab7 inactivation, which indicates either activation of a Rab7 GAP protein, or inactivation of the Rab7 GEF protein. It has been well documented that many GAP proteins mostly acting on Arf proteins are activated by PI(4,5)P 2 (Roy et al , ). On the other hand, to our knowledge no study has reported inositol lipids inhibiting a GEF protein.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, increased PI(4,5)P 2 production caused Rab7 inactivation, which indicates either activation of a Rab7 GAP protein, or inactivation of the Rab7 GEF protein. It has been well documented that many GAP proteins mostly acting on Arf proteins are activated by PI(4,5)P 2 (Roy et al , ). On the other hand, to our knowledge no study has reported inositol lipids inhibiting a GEF protein.…”
Section: Resultsmentioning
confidence: 99%
“…BRAG1/IQSec2 binds to Ca 2+ -free calmodulin in vitro, and addition of Ca 2+ causes its dissociation from membranes (Aizel et al. , 2013; Roy et al. , 2016).…”
Section: Arf Gefsmentioning
confidence: 99%
“…Pathogenic variants are located within the IQ‐like domain (Shoubridge et al., ; Zerem et al., ; Zhang et al., ), Sec7 domain (de Kovel et al., ; Gandomi et al., ; Helbig, et al ., ; Helm et al., ; Kalscheuer et al., ; Mignot et al., ; Shoubridge et al., ), or PH domain (Helm et al., ; Mignot et al., ). The IQ‐like and Sec7 functional domains are both involved in catalytic activity of guanine nucleotide exchange and activation of the substrate ARF6, while the PH domain may be involved in IQSEC2‐accessory protein interactions, increasing the association of substrates (ARFGDP) with the catalytic Sec7 domain or recruiting IQSEC2 and associated signaling pathways to different subcellular compartments via interactions with phosphoinositides (Roy, Yohe, Randazzo, & Gruschus, ). Hence, the consequences of missense changes in these domains may cause a partial loss of IQSEC2 function either by impaired ARFGEF activity or mislocalization of IQSEC2 (Kalscheuer et al., ; Shoubridge et al., ).…”
Section: Genotype–phenotype Relationships Of Pathogenic Variants In Imentioning
confidence: 99%